Were there regime switches in U.S. monetary policy? - Christopher A. Sims; Tao Zha (Federal Reserve Bank of Atlanta, 2004)
A multivariate model, identifying monetary policy and allowing for simultaneity and regime switching in coefficients and variances, is confronted with U.S. data since 1959. The best fit is with a model that allows time variation in structural disturbance variances only. Among models that also allow for changes in equation coefficients, the best fit is for a model that allows coefficients to change only in the monetary policy rule. That model allows switching among three main regimes and one rarely and briefly occurring regime. The three main regimes correspond roughly to periods when most observers believe that monetary policy actually differed, and the differences in policy behavior are substantively interesting, though statistically ill determined. The estimates imply monetary targeting was central in the early '80s but was also important sporadically in the '70s. The changes in regime were essential neither to the rise in inflation in the '70s nor to its decline in the '80s.
Keywords: 330; Geldpolitik; USA